Catalytic performance of spray-dried Cu/ZnO/Al2O3/ZrO2 catalysts for slurry methanol synthesis from CO2 hydrogenation. (September 2016) - Zhang, Yanfei; Zhong, Liangshu; Wang, Hui; Gao, Peng; Li, Xiaopeng; Xiao, Shuo; Ding, Guoji; Wei, Wei; Sun, Yuhan
Graphical abstract: Highlights: Micro-spherical Cu/ZnO/Al2 O3 /ZrO2 catalysts are prepared by spray drying. Addition of adequate amount of alumina sol enhances attrition resistance markedly. The attrition resistance plays an important role on performance in slurry reactor. The catalyst with addition of 10 wt.% alumina sol shows the best performance. Abstract: A series of Cu/ZnO/Al2 O3 /ZrO2 micro-spherical catalysts with different weight percentages of alumina sol from 0 to 20 wt.% are prepared by spray drying method. The as-obtained catalysts are first tested in the fixed-bed reactor for CO2 hydrogenation to methanol. When the added alumina sol is below 10 wt.%, the CO2 conversion is close to the equilibrium conversion of CO2 (26.5%) at 523 K and 5 MPa. Further increase of alumina sol content decreases the activity due to the decreased Cu surface area and weakened interaction among Cu and ZnO. When used in slurry bed, attrition resistance of catalysts plays an important role to determine the final catalytic performance. The catalyst without addition of alumina sol possesses low attrition resistance, which leads to catalyst loss and deactivation during reaction process. The introduction of suitable amount of alumina sol can enhance the attrition resistance of the catalysts markedly, and the catalytic activity can be still maintained at a high value. The spray-dried Cu/ZnO/Al2 O3 /ZrO2 catalyst with addition of 10 wt.% alumina sol exhibits the best performance with high activity and high stability.